Disruption of Hars2 in Cochlear Hair Cells Causes Progressive Mitochondrial Dysfunction and Hearing Loss in Mice - Xu, Pengcheng; Wang, Longhao; Peng, Hu; Liu, Huihui; Liu, Hongchao; Yuan, Qingyue; Lin, Yun; Xu, Jun; Pang, Xiuhong; Wu, Hao; Yang, Tao (Frontiers in Cellular Neuroscience, 2021)
Mutations in a number of genes encoding mitochondrial aminoacyl-tRNA synthetases lead to non-syndromic and/or syndromic sensorineural hearing loss in humans, while their cellular and physiological pathology in cochlea has rarely been investigated in vivo. In this study, we showed that histidyl-tRNA synthetase HARS2, whose deficiency is associated with Perrault syndrome 2 (PRLTS2), is robustly expressed in postnatal mouse cochlea including the outer and inner hair cells. Targeted knockout of Hars2 in mouse hair cells resulted in delayed onset (P30), rapidly progressive hearing loss similar to the PRLTS2 hearing phenotype. Significant hair cell loss was observed starting from P45 following elevated ROS level and activated mitochondrial apoptotic pathway. Despite of normal ribbon synapse formation, whole-cell patch clamp of the inner hair cells revealed reduced calcium influx and compromised sustained synaptic exocytosis prior to the hair cell loss at P30, consistent with the decreased supra-threshold wave I amplitudes of the auditory brainstem response. Starting from P14, increasing proportion of morphologically abnormal mitochondria was observed by transmission electron microscope, exhibiting swelling, deformation, loss of cristae and emergence of large intrinsic vacuoles that are associated with mitochondrial dysfunction. Though the mitochondrial abnormalities are more prominent in inner hair cells, it is the outer hair cells suffering more severe cell loss. Taken together, our results suggest that conditional knockout of Hars2 in mouse cochlear hair cells leads to accumulating mitochondrial dysfunction and ROS stress, triggers progressive hearing loss highlighted by hair cell synaptopathy and apoptosis, and is differentially perceived by inner and outer hair cells.